2019
DOI: 10.22159/ajpcr.2019.v12i1.28418
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities and Chemoprofiling Comparisons of Chenopodium Ambrosioides L. And Chenopodium Botrys L. Growing in Kashmir, India

Abstract: Objectives: The objectives of the study were the gas chromatography-mass spectrometry (GC-MS) identification and comparison of the chemical constituents, evaluation of the antifungal and anticancer activities of two species of genus Chenopodium, for example, Chenopodium ambrosioides (Ca) and Chenopodium botrys (Cb) growing in Kashmir, Himalayan region.Methods: The hydrodistilled essential oil of Ca and Cb was subjected to GC-MS analysis and antifungal activity for minimum inhibitory concentration (MIC) determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Moreover, 1-methyl-4-(1-methylethenyl)-2-cyclohexene-1-ol, as a new derivative in the substance, was previously detected in the chemical composition of Achillea santolina L. essential oil and demonstrated effectiveness against microorganisms and leishmania [ 56 ]. The compound trans-ascaridol, which was also identified amongst the main constituents of the Indian Chenopodium ambrosioides and Chenopodium botrys , has been found to have antifungal activity [ 57 ]. Interestingly, alloaromadendrene has been reported to have a higher antimicrobial activity than 1,8-cineole and to increase its antimicrobial potential [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 1-methyl-4-(1-methylethenyl)-2-cyclohexene-1-ol, as a new derivative in the substance, was previously detected in the chemical composition of Achillea santolina L. essential oil and demonstrated effectiveness against microorganisms and leishmania [ 56 ]. The compound trans-ascaridol, which was also identified amongst the main constituents of the Indian Chenopodium ambrosioides and Chenopodium botrys , has been found to have antifungal activity [ 57 ]. Interestingly, alloaromadendrene has been reported to have a higher antimicrobial activity than 1,8-cineole and to increase its antimicrobial potential [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies on D. ambrosioides oil have suggested that there are many chemotypes, for example, India oils, with the following major components: α-terpinene (65.4%), and p -cymene (29.4%) 38 ; α-terpinene (63.6%), p -cymene (19.5%), and ascaridole (6.2%) 39 ; α-terpinene (44.7%), p -cymene (21.3%), and ascaridole (17.9%) 40 ; ascaridole (38.0%), α-terpinene (37.7%), and p -cymene (16.7%) 41 ; ascaridole (40.7%), isoascaridole (22.7%), α-terpinene (17.9%), and p -cymene (8.5%) 42 ; p -cymene (36.3%) and ascardiole (31.2%) 21 ; α-terpinene (37.2%), isoascaridole (20.5%), and ascaridole (14.8%) 43 ; and α-terpinene (72.5%), p -cymene (20.6%), and terpinolene (2.5%). 44 In China, the D. ambrosioides oil was found to contain the following major components: menthol (31.3%), and α-terpinene (13.2%) 45 ; bornylene (42.6%), p -cymene (21.8%), ascaridole (18.4%), and α-terpinene (11.7%) 46 ; p -cymene (49.6%), α-terpinene (26.8%), and isoascaridole (8.2%) 47 ; ( Z )-ascaridole (29.7%), isoascaridole (13.0%), and p -cymene (12.7%) 48 ; and α-terpinene (32.9%) and p -cymene (24.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies demonstrate the cytotoxic activity of D. ambrosioides L. EO against tumours; the authors have demonstrated that the EO reduced cell growth and were cytotoxic to human breast cancer cell lines MCF-7 in a dose and time-dependent manner, via an apoptosis-related mechanism. D. botrys EO showed maximum growth inhibitions against the A549 cell line and inhibited the growth of the MCF-7 cell line ( Table 4 ) ( Shameem et al, 2019 ). The reported research has shown the precise anti-tumor mechanisms of D. ambrosioides EO, which are related to apoptosis induction ( Table 4 ).…”
Section: Health Benefitsmentioning
confidence: 99%